233k views
4 votes
Match each expression with an equivalent expression.

Question 4 options:

6x−4y

6−4x

6x−4x

6x−4

1. 2x
2. 2(3x−2)
3. 2(3−2x)
4. 2(3x−2y)

User Danfordham
by
5.6k points

2 Answers

6 votes

Answer:

6x-4y=2(3x-2y),

6-4x=2(3-2x),

6x-4x=2x,

6x-4=2(3x-2)

Explanation:

We have been given 4 expressions

6x−4y, 6−4x, 6x−4x, 6x−4

Now we need to simplify or factor so that we can match each expression with an equivalent expression.

6x-4y=2(3x-2y)

6-4x=2(3-2x)

6x-4x=2x

6x-4=2(3x-2)

Now we can easily see that right side is unique for each of the given expression which can be easily matched with given choices.

User Karpak
by
5.7k points
4 votes

Answer:


6x-4y → 4.
2(3x-2y)


6-4x → 3.
2(3-2x)


6x-4x → 1.
2x


6x-4 → 2.
2(3x-2)

Explanation:

You need to:

Factor out 2 from
6x-4y, then you get the equivalent expression:


=2(3x-2y) this matches with OPTION 4

Factor out 2 from
6-4y, then you get the equivalent expression:


=2(3-2x) this matches with OPTION 3

Make the subtraction for
6x-4x, then you get the equivalent expression:


=2x this matches with OPTION 1

Factor out 2 from
6x-4, then you get the equivalent expression:


=2(3x-2) this matches with OPTION 2

User Gobinath
by
5.3k points